Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1177/0146167211418531
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Threatened About the Future

Abstract: In many Western countries, the proportion of the population that is White will drop below 50% within the next century. Two experiments examined how anticipation of these future ethnic demographics affects current intergroup processes. In Study 1, White Americans who viewed actual demographic projections for a time when Whites are no longer a numerical majority felt more angry toward and fearful of ethnic minorities than Whites who did not view future projections. Whites who viewed the future projections also f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(124 citation statements)
references
References 47 publications
(73 reference statements)
2
115
0
1
Order By: Relevance
“…The only relation that was present in this study was the one between perceived diversity and anti-immigrant feelings. More recent research has confirmed these findings (Weins 2011;Outten et al 2012).…”
Section: Group Conflict Theory and Out-group Sizementioning
confidence: 63%
“…The only relation that was present in this study was the one between perceived diversity and anti-immigrant feelings. More recent research has confirmed these findings (Weins 2011;Outten et al 2012).…”
Section: Group Conflict Theory and Out-group Sizementioning
confidence: 63%
“…There is some evidence for this idea. For instance, Outten, Schmitt, Miller, and Garcia (2012;Study 2) showed that White Canadians who were informed that they will soon no longer be the numerical majority in Canada reported greater anger and fear towards minorities as well as greater sympathy towards White Canadians. Threat was assessed in part via agreement that White Canadians will have little influence on Canadian society in the future-a measure of collective efficacy concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Study 1 investigated British people's willingness to engage in collective action against immigrants. Participants were informed that in 40 years the proportion of immigrants in Britain is likely to stay the same (control condition) or that in 40 years the number of immigrants is likely to be greater than the number of White people (threat condition; for a similar manipulation, see Outten et al, 2012). Participants then indicated the extent to which they felt three emotions (angst, fear, and anger), prejudice toward immigrants, and willingness to engage in collective action against immigrants.…”
Section: Studymentioning
confidence: 99%
“…However, disadvantaged groups can threaten the advantaged group's distinct and prestigious social identity (for a review, see Jetten, Spears, & Postmes, 2004). Such threats are likely to increase prejudice toward disadvantaged groups (Esses, Medianu, & Lawson, 2013;Stephan, Renfro, Esses, Stephan, & Martin, 2005) and result in advantaged group members experiencing a variety of aversive emotions (Outten, Schmitt, Miller, & Garcia, 2012;Wohl & Branscombe, 2009). However, there has been little research assessing the extent to which these factors motivate advantaged groups to undertake collective action against the disadvantaged group.…”
Section: Introductionmentioning
confidence: 99%